Early detection of bowel disease in symptomatic patients attending community pharmacies - Sriram, Deepa (Curtin University, 2016)
With evidence that a substantial number of individuals manage symptoms without seeking medical help, a pharmacy service with symptom management guided by a screening tool should assist in the triage of clients with underlying health conditions. This research describes the successful development, validation and testing of an assessment questionnaire to guide pharmacy staff in identification of pharmacy clients at risk of serious bowel conditions, with referral of clients for further investigation where warranted.